A vivência do luto em situações de desastres naturais - Torlai, Viviane Cristina (2010)
Natural disasters cause disruption in the lives of those involved, leaving the suddenly bereaved, there are both material and psychological losses to the population. Affect patterns of community and their network of psychosocial support, placing at risk the ability of individual and collective coping. This study aimed to examine the experience of mourning for people who have suffered losses from disasters, specifically floods in the city of Blumenau, SC, in December 2008. Was held in the city of Blumenau, in Santa Catarina, housing the participants. Five people participated in this survey, over 21 years, who attended the calamity of 2008 and currently reside in temporary housing or receive rental income and presenting award interdiction of residence, making it impossible to return to her family. A semistructured interview was conducted with minimal pre-structuring from a semi-structured. Through content analysis, the information was discussed with the mourning process characterized by the experience of traumatic events. In the narrative of the participants were able to identify the impact on the disaster and the fall in world presumed because the unpredictability of life, forecasts of future control of events and vulnerability, leading to loss of sense of security and protection. The disaster led to a succession of losses, since the material loss to the loss of the psychological identity of individuals and the community. It was observed that mourning for disasters is a continuous process of development of losses that requires the mourner's internal and external resources to cope with the traumatic situation. The coping resources found to support the traumas and losses was social support, faith and religion. Complete this study is to pave the way for new thoughts and questions about the losses resulting from disaster, trying to broaden the look at the quality of care for survivors, developing activities that promote the development of the mourning process by disasters